Economic analysis comparing continuous cover forestry and rotation forestry with genetic gain in Norway spruce stands - Lee, Daesung; Ahtikoski, Anssi; Siipilehto, Jouni; Repola, Jaakko; Kärkkäinen, Katri; Lehtonen, Mika; Hynynen, Jari (Oxford University Press, 2026)
Growing interest in continuous cover forestry (CCF) has led to an increasing need to compare between CCF and rotation forestry (RF). Here, we introduce the effect of genetic gain into the financial comparison between RF and CCF in Norway spruce (Picea abies (L.) Karst.) stands. We applied two datasets: (i) five experimental plots treated with selection cuttings (standing timber a priori favouring CCF) and (ii) identical locations and site types corresponding to those five plots, representing bare land cases. A stand-level optimisation framework was applied to maximise net present value for both CCF and RF. The results showed that CCF outperformed RF when the comparison was made from standing timber, regardless of site type (mesic heath or herb-rich) or interest rate (3% or 5%). When starting from bare land, both site type and interest rate played a crucial role: at a 3% interest rate, RF outperformed CCF on both site types—this applied with and without genetic gain associated with RF. At a 5% interest rate, on mesic heath sites, CCF became financially more attractive than RF, both with and without genetic gain. Furthermore, on herb-rich sites, only RF with genetic gain outperformed CCF at the 5% interest rate. Overall, this study has successfully analysed the financial comparison between CCF and RF, incorporating the effect of genetic gain into RF, and provides fundamental insights and valuable information to support economic decision-making in the management of Norway spruce stands.
Keywords: Stand-level optimization; genetic gain; continuous cover forestry; rotation forestry; Norway spruce